Biomass-based composite catalysts for catalytic wet peroxide oxidation of bisphenol A: Preparation and characterization studies. Issue 3 (June 2019) - Juhola, Riikka; Heponiemi, Anne; Tuomikoski, Sari; Hu, Tao; Prokkola, Hanna; Romar, Henrik; Lassi, Ulla
Graphical abstract: Highlights: The optimized conditions for the granulation of biomass-based carbon were studied. Carbon combined with metakaolin, CaO and NaOH produced stable composite granules. The most stable composites were tested in catalytic wet peroxide oxidation of BPA. The catalytic activity of composites was higher than powdered carbon raw material. Catalytic activity is based on surface functionality and basicity of composites. Abstract: The wet granulation process was used to prepare new, efficient, and cost-effective granular biomass-based composite catalysts for catalytic wet peroxide oxidation (CWPO) of bisphenol A (BPA). The most stable composite granules was prepared by mixing biomass-based carbon residue (CR) with metakaolin (MK) combined with calcium oxide (CaO) or cement and a solvent (NaOH or KOH). For all the prepared composite granules, the optimized binding agents to carbon ratio was 0.3, the solvent to carbon ratio 1.2, and the agitation rate 1200 rpm. The specific surface area of the prepared catalysts was 152–205 m 2 /g. The composite granular catalyst (CR + MK + CaO + NaOH) had the most durable and stable structure (compressive strength of 27 N) and the most basic surface (15 mmol/g) measured with temperature programmed desorption. This catalyst was the most active in CWPO of BPA and total organic carbon removal of 50% and 48%, respectively.